Relations between the Soviet Lithuanian Government and the Baltic Military District in 1963–1986 - Arlauskaitė , Inga (Genocidas ir rezistencija, 2006)
The Soviet annexation of Lithuania was also manifested in aspects such as supplying the Soviet army with the required resources. The influence of the Soviet army and the relations between the armed forces and the local authorities in Lithuania has not been thoroughly investigated. A study of the relations between the Soviet Lithuanian government and the Baltic Military District draws on numerous archival materials of 1963–1986, and reveals the basic tendencies in the relations. The influence of the Soviet military ethos is the primary characteristic of the relations between the Soviet army and the local authority. According to the Soviet military doctrine, the Soviet Union was expecting the potential use of nuclear weapons by Western countries, and was preparing for war. The Soviet republics, including Lithuania, had to implement prescriptions initiated in Moscow for preparations for war. Changes in the military doctrine influenced changes in the military and military-social demands. The demands of the military involved mainly requirements to enlarge the land possessions of the Baltic Military District and its garrisons, to provide the military with accommodation, to improve the condition of the country's roads, the mobilization of agricultural machinery, and the mobilization of people into the Soviet army. To meet the demands of the military, the Lithuanian government usually used local resources.Relations between the Soviet Lithuanian government and the Baltic Military District in the sphere of land assignations had no united model. In the period 1963–1986 a substantial change in relations took place, increasing the number of failures to satisfy the military's requests. The consumption of Lithuanian forests by the military was one of the factors that influenced the changes in relations between the Baltic Military District and the Lithuanian government. The control of the exploitation of forests was a sphere where the Soviet Lithuanian authority expressed a particular position with regard to Soviet Lithuania's economic interests. The relations between the Soviet Lithuanian government and the Baltic Military District depended on the possibility of the local authority to provide the army with accommodation. To guarantee the military housing, the Lithuanian government established the „10 percent fee“ and also developed mass construction works. Nevertheless, in the Seventies, Lithuania fell into debt supplying accommodation to the Baltic Military District. The Soviet army did not always occupy a superior and inflexible place in Soviet Lithuania. In the Eighties some alterations between the Soviet Lithuanian government and the Baltic Military District relations in the field of mobilization potential were effected. Organizations and companies in Soviet Lithuania disregarded the implementation of military mobilization schedules. Periodically, in people's attitude towards So military service, changes appeared.
Keywords: Soviet occupation; communist party; Soviet army; executive power